PENGARUH PENAMBAHAN KAYU MANIS (Cinnamomum Verum) TERHADAP KUALITAS ORGANOLEPTIK PADA TELUR ASIN - Badiyatunnajah, Hilma; Adyatama, Aqil (Fakultas Pertanian Universitas Garut, 2025)
Duck eggs are one of the animal proteins derived from ducks that have a delicious taste, are easy to digest and have high nutritional content. The high nutritional content makes eggs a medium for the growth of bacteria that make eggs easily damaged or perishable food, so it is necessary to preserve eggs in order to extend the shelf life of duck eggs. The manufacture of salted eggs generally only uses the addition of salt, so that it will produce original salted eggs. However, there have been several studies and innovations that have been carried out to improve the quality and variety of salted eggs, one of which is by adding natural ingredients as another alternative. One of the ingredients that can be used is cinnamon (Cinnamomum verum), because this ingredient contains compounds that can affect the organoleptic quality of food products. This study aims to examine the effect of adding cinnamon on the organoleptic quality of salted eggs, namely aroma, taste and texture. This study was conducted experimentally which was arranged based on a completely randomized design (CRD) with the addition of cinnamon divided into 4 treatments (0; 7.5; 15; 22.5 grams) which were repeated 5 times. The data obtained were analyzed using one-way ANOVA and further tested using Duncan's Multiple Range Test (DMRT) with IBM SPSS 26. The results showed that the addition of cinnamon up to 22.5 grams to salted eggs did not significantly affect the aroma with a value of 2.53-2.95 (fishy-slightly fishy), taste 3.09-3.80 (slightly salty) and texture 3.28-3.41 (slightly dense). The conclusion of this study is that the addition of cinnamon up to 22.5 grams does not change the aroma, taste and texture of salted eggs.